Pelatihan Wawasan Politik Islam Pada Siswa MAS Darul Hikmah Meureubo Kabupaten Aceh Barat - Vellayati Hajad; Ikhsan Ikhsan; Akmal Saputra; Nellis Mardhiah; Nodi Marefanda; Cut Irna Liyana (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
The younger generation is an important pillar of the state. At the same time, they hold ideology and action. On the basis of a historical approach, Muslim youth contributed significantly to the establishment of Indonesia during the period of independence until the 1998 reform period. However, there is currently a decline in the participation of Muslim youth in politics. There are many reasons, including passive attitudes towards national political problems and the still low level of literacy of Islamic politics among young people. It is therefore important to do this dedication, which aims to increase the political understanding of Islam among the young generation of Islam. The method used is the format of lectures, discussions and question and answer sessions. Before and after the test, it was shown that there was an increase in Islamic political insight among students compared to before the activity was carried out.